Proteção parical à infecção por L. amazonensis na infecção concomitante com L. major - Claudia Zuleida Gonzalez Lombana (2008)
Experimental murine infections with Leishmania spp. that cause cutaneous leishmaniasis has led to an understanding of many immunological events that are required for a successful host response towards these protozoan parasites. Many studies have demonstrated that the host response is determined by the species or strains of Leishmania and also that this response may vary in the same mouse strain. Since C57BL/6 mice infected with L. major develop a Th1 response that leads to spontaneous resolution of lesions and knowing that the susceptibility of these mice to L. amazonensis results from an inability to mount these responses, we tested the hypothesis that the previous induction of a response elicited by L. major would modify the outcome of infection with L. amazonensis. To address this issue, C57BL/6, IL-10-/- and 2M-/- mice, which had been previously inoculated into the left hind footpad with 1 x 104 metacyclic promastigotes of L. major, were infected with 104 metacyclic promastigotes of L. amazonensis in the contralateral footpad and the course of infection was followed for 10 weeks. We have demonstrated that C57BL/6 mice previously -infected with L. major restrain pathogenic responses induced by L. amazonensis infection. This process is related in part with a partial resistance, which is independent of IL-10, as evidenced by moderate reduction in parasite number within L. amazonensis lesions from pre-infected wild-type and IL-10-/-mice. We found a higher production of IFN- by spleen cells from pre-infected mice at weeks 6 and 10 after L. amazonensis-infection, but IFN--production by draining lymph node cells was not different between pre-infected mice and their control counterpart. In contrast, pre-infected mice showed high TNF- and iNOS mRNA expression at the site of infection. In addition, mice depleted of T CD8+ cells controlled immunopathology, on the contrary, mice genetically deficient in CD8+ T cells (2M-/-) did not. To understand how pre-infected mice controlled progression L. amazonensis lesions without marked reduction of number parasites, we examined chemokines production at the site of infection and frequency and phenotypes of T cells in the draining lymph nodes at various time points using flow cytometry. Our findings show reduced recruitment of monocytes and lymphocytes in L. amazonensis lesions, differential production of CCL3/MIP-1 and CCL5/RANTES and a increased frequency of CD8+ Tsup and CD4+ Treg cells at the draining lymph nodes, which is consistent with our hypothesis that the restrained lesion progression in pre-infected mice is markedly associated with a altered cell recruitment to the site of infection and early induction of T cells bearing the regulatory phenotype.